Legitimasi Normatif dan Kerangka Yuridis Sanksi Hakim Pelanggar Etika dalam Sistem Peradilan Indonesia - Khofifah Magfirah; Abdullah Talli; Zuhasari Mustafa (Media Hukum Indonesia (MHI), 2025)
Judges play a central role in upholding justice and maintaining the integrity of the judiciary. However, various cases of ethical and legal violations indicate that not all judges carry out this mandate optimally. This study aims to explain the normative and juridical foundations for imposing sanctions on judges who violate the law, analyze the regulation of judicial codes of ethics within the Indonesian legal system, and assess the implications of ethical violations on public trust. This research employs a normative legal method through a juridical-normative approach by examining literature on fiqh al-qadha (the Qur’an, Hadith, and classical fiqh texts), statutory regulations, and judicial codes of ethics. The analysis is conducted qualitatively by interpreting legal norms and principles of judicial ethics. The findings show that fiqh al-qadha emphasizes the obligation of judges to uphold justice and prohibits decisions influenced by personal interests, providing a strong normative basis for imposing sanctions for ethical violations. From a legal perspective, sanctions against judges are regulated in the Law on Judicial Power, the Code of Ethics and Code of Conduct for Judges (KEPPH), as well as joint regulations between the Supreme Court and the Judicial Commission, which provide for sanctions ranging from light to severe. This study also concludes that ethical violations have a direct impact on declining public trust, undermine the legitimacy of the courts, and threaten social stability. Therefore, the enforcement of codes of ethics and sanctions is an essential instrument in maintaining the integrity of judicial institutions.